A note on recruiting intensity and hiring practices: Cross-sectional and time-series evidence - Ben Lochner; Christian Merkl; Heiko Stüber; Nicole Gürtzgen (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2019)
Using the IAB Job Vacancy Survey for Germany, we look into the black box of recruiting intensity and hiring practices. Our paper shows three important channels for hiring, namely vacancy posting, the selectivity of hiring (labor selection), and the number of search channels. While vacancy posting and labor selection show a U-shape over the employment growth distribution, the number of search channels tends to be upward sloping in terms of employment growth. We argue that shrinking plants post more vacancies and are less selective than plants with a constant workforce because they react to churn triggered by employment-to-employment transitions to other plants. Furthermore, in line with economic theory, vacancy posting, labor selection, and the number of search channels are procyclical over the business cycle. Our paper is the first to link the the Job Vacancy Survey and the Administrative Wage and Labor Market Flow Panel to document the interaction between hiring practices and employment-to-employment transitions to other plants.
Keywords: E24; J63; 330; recruiting intensity; vacancies; labor selection; administrative data; survey data